PENGGUNAAN BAHASA INDONESIA PADA MEDIA RUANG PUBLIK DI KOTA PEKANBARU - Fatmahwati A, Fatmahwati A (SUAR BETANG, 2018)
This paper discusses use of Indonesian at public places in Kota Pekanbaru and this study aims to describe use of the language at public places and influencing actors. By using the descriptive analytic method and interpretative technique, data were analyzed with reference to literature review. The data of this study are words, phrases, and sentences used at public places media such as billboards, banners, and posters. The data are collected through observation and interview. The research findings reveal the most dominant phenomenon is the use of foreign languages and the use of Indonesian language that does not meet rules of Indonesian. The reasons for using foreign languages are: (1) respondents do not know that there is a regulation stipulating the use of Indonesian at public places, (2) they assume foreign languages have higher prestige, (3) they believe people like foreign languages better than Indonesian, and (4) they assume foreign terms are more commonly used. The reasons for misuse of Indonesian rules are: (1) respondents do not know Indonesian rules, (2) they assume Indonesian rules are not important, and (3) they believe that people do not cencern with the language rules. In addition, they tend to ignore rules of Indonesian. The linguistic landscape of the language of public spaces in Pekanbaru City informationally and symbolically shows that the existence of Indonesian is increasingly fading with the rise of the use of  foreign languages.